B Corps: A Socioeconomic Approach for the COVID-19 Post-crisis - Saiz-Álvarez, José Manuel; Vega-Muñoz, Alejandro; Acevedo-Duque, Ángel; Castillo, Dante (Frontiers in Psychology, 2020)
The current global health and economic crisis caused by COVID-19 has opened the possibility to adopt the B Corp model to person-focused. Based on grounded theory, we have examined 147 organizations from 14 countries listed at the B Corp Directory for Latin America. Latin American B Corps have traits linked to family-related issues that are distinct from other B Corps located in different continents. Our main findings are that B Corps develop a more inclusive and sustainable economy to benefit society, go beyond the notion of CSR, and move away from traditional companies, as B Corps combine social development and economic growth.